Brand Loyalty at Chain Hotel in Denpasar - Wisnawa, I Made Bayu (E-Journal of Tourism, 2018)
Purposes of this research are: (i) to find out the influence of brand image toward customer satisfaction (ii) to find out the influence of customer satisfaction toward brand loyalty (iii) to find out the influence of brand image toward brand loyalty and (iv) to find out the role of customer satisfaction as a mediating variable between brand image and brand loyalty. Structural Equation Modelling (SEM) was developed to answer the research problems. The number of respondent was 150 which was collected through offline and online self-administered questionnaire. There were 13 indicators used to measure each construct. The results show that (i) brand image positively and significanly influence customer satisfaction, (ii) customer satisfaction positively and significantly influenced brand loyalty, (iii) brand image did not influence brand loyalty, and (iv) customer satisfaction did not mediate the relationship between brand image toward brand loyalty. Keywords : brand image, customer satisfaction, brand loyalty